a) 8x^3-1 = 2³x³ - 1³ = (2x - 1)(4x²+2x+1)
b) 2x^3-6x^2+3x-9 = 2x²(x-3) + 3(x-3) = (2x²+3)(x-3)
c) 3x^3-3x^2-6x = 3x(x²-x-2) = 3x(x-2)(x+1)
That's it!
Good luck!
2007-01-09 09:24:04
·
answer #1
·
answered by CHESSLARUS 7
·
0⤊
1⤋
a) 8x^3 -1
= 2^3x^3 - 1^3
= (2x)^3 - 1^3
= (2x - 1)(4x^2 + 2x + 1)
b) 2x^3 - 6x^2 + 3x - 9
= 2x^2 (x - 3) + 3(x - 3)
= (2x^2 + 3)(x - 3)
c) 3x^3 - 3x^2 - 6x
= 3x (x^2 - x - 2)
= 3x (x - 2)(x + 1)
2007-01-10 07:22:05
·
answer #2
·
answered by Kinu Sharma 2
·
0⤊
0⤋
1) ==> 8x^3-1 = 2³x³ - 1³ = (2x - 1)(4x²+2x+1)
2) ==> 2x^3-6x^2+3x-9 = 2x²(x-3) + 3(x-3) = (2x²+3)(x-3)
3) ==> 3x^3-3x^2-6x = 3x(x²-x-2) = 3x(x-2)(x+1)
2007-01-10 11:03:23
·
answer #3
·
answered by Prakkhar Gupta 1
·
0⤊
0⤋
8x^3-1=(2x-1)(4x^2+2x+1)
2x^3-6x^2+3x-9= 2x^2(x -3) +3(x-3)= (2x^2+3)(x-3)
3x^3-3x^2-6x = 3x(x^2-x-2)=3x(x-2)(x+1)
2007-01-09 17:33:14
·
answer #4
·
answered by ironduke8159 7
·
0⤊
0⤋
i think that 8x^3-1 stays as it is, 2x^3-6x^2+3x-9 is -4x+3x-9, and 3x^3-3x^2-6x is x-6x...... sorry if im wrong....
2007-01-09 17:20:21
·
answer #5
·
answered by ♥2cute4u♥ 3
·
0⤊
1⤋
Yes I can
2007-01-09 17:18:50
·
answer #6
·
answered by Anonymous
·
0⤊
2⤋
e + mc & flux capacitor.com
2007-01-09 17:17:26
·
answer #7
·
answered by flavorlicious 2
·
0⤊
2⤋
you are soo cheating !
2007-01-09 17:48:48
·
answer #8
·
answered by amal L 3
·
0⤊
0⤋
no lol i'm in pre-algebra not good
2007-01-09 17:18:16
·
answer #9
·
answered by auttiemarie03 2
·
1⤊
1⤋
um do it with your calculator. lol.
2007-01-09 17:18:34
·
answer #10
·
answered by Anonymous
·
0⤊
1⤋